Seguimiento de los egresados de la Facultad de Odontología de la Universidad de Antioquia desde 1941 hasta el 2011. Parte III. Vínculo facultad-egresado e impacto social del programa (2014)
ABSTRACT: The link of the institutions of higher education with its graduates is critical in curricular feedback to ensure the relevance and quality of the education provided. The purpose of this third part of the research was to determine the degree of satisfaction that the graduates have with the knowledge acquired, besides knowing the relationship they have with their college and union institutions. Methods: this was a descriptive, retrospective, crosssectional, with structured survey, triangulated, validated and pilot. Ethical principles were respected and guaranteed the confidentiality of information. Results: 91% graduates are very satisfied with the training received. They believe that their education provided tools for work performance. Regarding the academic relationship with the School after graduation, 40.4% consider that the relationship is not very close. The 21.8% of the graduates have started one or more companies; in general, graduates of the school belong to some kind of unionization, either scientific-academic, corporate, cooperative, and cultural and recreational. Conclusions: the graduates recognize the training as one of very good quality and very comprehensive, overall feel gratitude for their school, but do not feel very close.